Cerebral oxygenation and body position in the preterm infant: A systematic review and meta‐analysis. (11th October 2022) - Maes, Eva; Cools, Filip; Dereymaeker, Anneleen; Jansen, Katrien; Naulaers, Gunnar; Thewissen, Liesbeth
Abstract: Aim: After preterm birth, supine head midline position is supported for stable cerebral blood flow (CBF) and prevention of intraventricular haemorrhage (IVH), while prone position supports respiratory function and enables skin‐to‐skin care. The prone compared to supine position could lead to a change in near‐infrared derived cerebral tissue oxygen saturation (rScO2), which is a surrogate for cerebral blood flow (CBF). By monitoring rScO2 neonatologists aim to stabilise CBF during intensive care and prevent brain injury. In this systematic review and meta‐analysis, we investigate the effect of the body position on rScO2. Methods: A comprehensive literature search was performed to identify all trials that included preterm infants in the first 2 weeks after birth and compared rScO2 in the prone versus supine head in midline position of the infant. A meta‐analysis, including two subgroup analyses based on postnatal age (PNA) and gestational age (GA), was performed. Results: Six observational cohort studies were included. In the second, but not the first week after birth, a significant higher rScO2 in the prone position was found with a mean difference of 1.97% (95% CI 0.87–3.07). No rScO2 difference was observed between positions in the extremely preterm nor the preterm group. Conclusion: No consistent evidence was found that body position influences rScO2 in the first 2 weeks after preterm birth. Subgroup analysis suggests that in the second week after birth, the prone position might result in higher cerebral rScO2 than the supine position with head in midline. Multiple factors determine the best body position in preterms.